New South Wales annual vaccine-preventable disease report, 2012 - Alexander Rosewell; Paula Spokes; Robin Gilmour (World Health Organization Regional Office for the Western Pacific, 2014)
We aim to describe the epidemiology of selected vaccine-preventable diseases in New South Wales (NSW) for 2012. Data from the NSW Notifiable Conditions Information Management System were analysed by: local health district of residence, age, Aboriginality, vaccination status and organism, where available. Risk factor and vaccination status data were collected by public health units for cases following notification under the NSW Public Health Act 2010. The largest outbreak of measles since 1998 was reported in 2012. Pacific Islander and Aboriginal people were at higher risk as were infants less than 12 months of age. Notifications of invasive pneumococcal disease (IPD) in children less than five years declined; however, the overall number of notifications for IPD increased. Mumps case notifications were also elevated. There were no Haemophilus influenzae type b case notifications in children less than five years of age for the first time since the vaccine was introduced. Invasive meningococcal disease case notifications were at their lowest rates since case notification began in 1991. Case notification rates for other selected vaccine-preventable diseases remained stable. Vaccine-preventable disease control is continually strengthening in NSW with notable successes in invasive bacterial infections. However, strengthening measles immunization in Pacific Islander and Aboriginal communities remains essential to maintain measles elimination.